2020
DOI: 10.1002/dev.21963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anesthesia exposure in early development on learning and sensory functions

Abstract: Each year, millions of children undergo anesthesia, and both human and animal studies have indicated that exposure to anesthesia at an early age can lead to neuronal damage and learning deficiency. However, disorders of sensory functions were not reported in children or animals exposed to anesthesia during infancy, which is surprising, given the significant amount of damage to brain tissue reported in many animal studies. In this review, we discuss the relationship between the systems in the brain that mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 119 publications
1
25
0
Order By: Relevance
“…However, as conditioned responses (CRs) were not completely abolished, the damage only partially disrupted learning-related pathways. Such deficits in learning reflect the cumulative impact of anesthesia-related damage as well as subsequent development and compensation by the brain 25 . In order to understand the nature of this damage, we used a number of MRI techniques to examine changes in key structures of the circuitry underlying trace ECC.…”
Section: Discussionmentioning
confidence: 99%
“…However, as conditioned responses (CRs) were not completely abolished, the damage only partially disrupted learning-related pathways. Such deficits in learning reflect the cumulative impact of anesthesia-related damage as well as subsequent development and compensation by the brain 25 . In order to understand the nature of this damage, we used a number of MRI techniques to examine changes in key structures of the circuitry underlying trace ECC.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of findings in animal models and cell culture studies have demonstrated that propofol can induce developmental neurotoxicity, raising serious concerns regarding the safety of pediatric propofol anesthesia (McInnis et al, 2002;Wang et al, 2000Wang et al, , 2010. The extent of this brain damage depends on the duration of anesthesia, the frequency of anesthesia exposure, and other factors related to the anesthesia protocol (Aksenov et al, 2020). Unfortunately, although many studies have found that propofol induces neurotoxicity in the developing animal brain, the specific mechanism of action remains largely unknown (Aksenov et al, 2020;Bosnjak et al, 2016;McInnis et al, 2002;Reitman & Flood, 2011;Wang et al, 2000Wang et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of this brain damage depends on the duration of anesthesia, the frequency of anesthesia exposure, and other factors related to the anesthesia protocol (Aksenov et al, 2020). Unfortunately, although many studies have found that propofol induces neurotoxicity in the developing animal brain, the specific mechanism of action remains largely unknown (Aksenov et al, 2020;Bosnjak et al, 2016;McInnis et al, 2002;Reitman & Flood, 2011;Wang et al, 2000Wang et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these previous reports of cellular injury in the cortex and thalamus, we found no difference in the magnitude and shape of the BOLD signal in the somatosensory cortex with whisker stimulation in either controls or anesthesiaexposed rabbits (Aksenov et al, 2016), which would indicate that the pathological effect of injury was not pronounced, at least on the functional level. A recent review (Aksenov et al, 2020a) concluded that the functions of the sensory systems are affected less by neonatal anesthesia than learning-related functions due to the stronger ability of the sensory system to compensate for significant structural damage. For example, the loss of 50% or more sensory fibers/neurons may not produce sensory deficiency.…”
Section: Discussionmentioning
confidence: 99%